Natural Law, Criminalization and Extraterritorial Jurisdiction in Thailand and China: A Comparative Law Perspective - Chitov, Alexandre (Connexion: Journal of Humanities and Social Sciences, 2018)
This paper examines the expending extraterritorial jurisdiction in Thailand and China in relation to criminal offences. It is argued that the expanding ambit of extraterritorial jurisdiction logically requires the presence of some limitations. There are certain limits that are imposed by international law on the sovereign states in relation to criminalization policies. They consists not only of ever-changing international agreements, but also of the universal principles of natural law. International law affirms such natural law principles as the prohibitions of double jeopardy and retroactivity of criminal laws. From a natural law perspective, the legislation and practice of both countries insufficiently reflect those prohibitions. Criminal laws in Thailand and China, being influenced by legal positivism, ignore a natural law approach in limiting extraterritorial effects of their criminal law policies. Ignoring fundamental natural law principles can lead to the situations of the conflict of jurisdictions, and more importantly to an unjustifiable criminalization of people beyond national borders.